Neurotoxic 1‐deoxysphingolipids and paclitaxel‐induced peripheral neuropathy. Issue 11 (21st July 2015) - Kramer, Rita; Bielawski, Jacek; Kistner‐Griffin, Emily; Othman, Alaa; Alecu, Irina; Ernst, Daniela; Kornhauser, ew; Hornemann, Thorsten; Spassieva, Stefka
ABSTRACT: Peripheral neuropathy is a major dose‐limiting side effect of paclitaxel and cisplatin chemotherapy. In the current study, we tested the involvement of a novel class of neurotoxic sphingolipids, the 1‐deoxysphingolipids. 1‐Deoxysphingolipids are produced when the enzyme serine palmitoyltransferase uses l ‐alanine instead of l ‐serine as its amino acid substrate. We tested whether treatment of cells with paclitaxel (250 nM, 1 μM) and cisplatin (250 nM, 1 μM) would result in elevated cellular levels of 1‐deoxysphingolipids. Our results revealed that paclitaxel, but not cisplatin treatment, caused a dose‐dependent elevation of 1‐deoxysphingolipids levels and an increase in the message and activity of serine palmitoyltransferase ( P < 0.05). We also tested whether there is an association between peripheral neuropathy symptoms [evaluated by the European Organization for Research and Treatment of Cancer (EORTC) QLQ‐chemotherapy‐induced peripheral neuropathy‐20 (CIPN20) instrument] and the 1‐deoxysphingolipid plasma levels (measured by mass spectrometry) in 27 patients with breast cancer who were treated with paclitaxel chemotherapy. Our results showed that there was an association between the incidence and severity of neuropathy and the levels of very‐long‐chain 1‐deoxyceramides such as C24 ( P < 0.05), with the strongest association being with motor neuropathy ( P < 0.001). Our data from cells and from patients with breast cancer suggest that 1‐deoxysphingolipids, the very‐long‐chain in particular, play a role as molecular intermediates of paclitaxel‐induced peripheral neuropathy.—Kramer, R., Bielawski, J., Kistner‐Griffin, E., Othman, A., Alecu, I., Ernst, D., Kornhauser, D., Hornemann, T., Spassieva, S. Neurotoxic 1‐deoxysphingolipids and paclitaxel‐induced peripheral neuropathy. FASEB J. 29, 4461‐4472 (2015). www.fasebj.org